The Early Transmission of al-Suhrawardī's ʿAwārif al-Maʿārif. - Kars, Aydogan (Journal of Religion, 2022)
This article traces the early transmission for ʿUmar al-Suhrawardī's (539–632/1145–1234) influential Sufi treatise Benefits of Intimate Knowledge (ʿAwārif al-Maʿārif). Analyzing the biographical dictionaries, authorization certificates (ijāza), and audition (samāʿ) records in the early copies of the work, it aims to produce an initial yet complex map of scholarly networks that formally disseminated al-Suhrawardī's masterpiece, with a focus on the first two centuries of its composition. These networks, as the article observes, go beyond the transmissions of the initiatic robe and the mystical formula of the Sufi order (ṭarīqa), insofar as some key figures in the early transmission were traditionists who neither received a Suhrawardian initiatic robe nor had any known connection with Sufism at large. The article suggests that the audition sessions of traditionist circles particularly in the Hijaz played a key role in the early transmission of ʿAwārif al-Maʿārif. Its transmission was part and parcel of the circulation of a broader set of works, those on prophetic traditions (ḥadīth) in particular, such as Musnad al-Dārimī , Ṣaḥīḥ al-Bukhārī , and Ṣaḥīḥ al-Muslim. We find ʿAwārif al-Maʿārif in a long list of transmitted ḥadīth works, often together with another Sufi treatise, Al-Risāla penned by al-Qushayrī (d. 465/1072).